Green Entrepreneurial Behavior: A Review and Research Agenda - Nadhifa, Safira Reza; Prabarini, Asri Meidina; Wati, Intan Ratna (Research Horizon, 2024)
The business world grapples with the persistent challenge of environmental sustainability. To foster environmentally conscious entrepreneurial practices, it's crucial to understand the factors influencing green entrepreneurial behavior. This paper examines the relationship between green entrepreneurial intention, green entrepreneurial behavior, and the role of social support, specifically from family members. Through a systematic literature review of 20 recent articles published between 2020 and 2024, the study investigates this critical connection. The study's findings highlight a crucial connection between social support, specifically from family, and the transition from green entrepreneurial intentions to actual green entrepreneurial behavior. This connection suggests that familial support plays a vital role in motivating and enabling individuals to translate their environmental aspirations into concrete actions. By understanding this dynamic, the research provides valuable guidance for both entrepreneurs and policymakers. This collaborative approach can significantly contribute to the widespread adoption of sustainable practices within the business world, ultimately benefiting both the environment and society as a whole.